2014
DOI: 10.1021/ac5024099
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Antibody Color Resulting from Advanced Glycation End Product Modifications

Abstract: Recombinant antibodies produced in Chinese hamster ovary (CHO) cells often exhibit a slight yellow-brown color, but the molecular basis for this color has remained elusive. We predicted that the color results from post-translational modifications on the antibody, because colored species were found to coelute with antibody products during size exclusion chromatography. Previously, modification by oxidation and advanced glycation end products (AGEs) had been shown to give rise to colored and fluorescent species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…Since there are multiple AGEs products, each kind of AGEs product needs to be quantitated separately. 16,21,60 In addition to lysine, arginine is a potential spot where AGEs modifications may occur in recombinant antibodies. 17 Isotope labeling has also been applied to antibody glycation analysis.…”
Section: Charge-based Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since there are multiple AGEs products, each kind of AGEs product needs to be quantitated separately. 16,21,60 In addition to lysine, arginine is a potential spot where AGEs modifications may occur in recombinant antibodies. 17 Isotope labeling has also been applied to antibody glycation analysis.…”
Section: Charge-based Methodsmentioning
confidence: 99%
“…63 NBT analysis was applied to glycated antibody by Ahmad, et al 39 in 2012. 37 Recently, Butko, et al 21 reported that several AGEs found in manufactured recombinant mAb were strongly related to a color change in the antibody solution, and that AGEs are partially responsible for the color of mAb products. 19 Additionally, an enzymelinked immunosorbent assay (ELISA) format has been applied to study the AGEs in mAbs, utilizing the binding between a sample and a biotin-conjugated primary antibody that targets a specific kind of AGEs.…”
Section: Colormetric Assaymentioning
confidence: 99%
See 3 more Smart Citations